Midseason screening for groin pain, severity, and disability in 101 elite American youth soccer players: a cross-sectional study - DeLang, M. D.; Garrison, J. C.; Hannon, J. P.; McGovern, R. P.; Sheedy, P.; Christoforetti, J. J.; Thorborg, K. (Clinical Journal of Sport Medicine, 2022)
Objective: To (1) systematically screen for groin pain and type in young elite soccer players and (2) assess whether hip and groin-related severity and disability differed between players with different levels of groin pain and tenderness.